Characterization of mitochondrial control region in Merlucciidae: sequence variation and molecular phylogeny - Crous, Marta; Roldán, María I (Zootaxa, 2015)
In order to describe the structure and evolution of Merlucciidae and related Gadiformes mitochondrial control region we analysed 470 bp of 31 taxa belonging to 28 different species. The general structure and conserved sequence blocks observed in Gadiformes mitochondrial control region are similar to those present in other teleost fishes. The length of this segment is variable among related species due to the presence of numerous indels at domain I. Domain II is the most conserved region with a high G content. The GTGGG-box is absent in all Merluccius and seven other Gadidae species. Several methods of phylogenetic analyses has revealed the monophyly of Gadiformes, Gadinae and Merlucciidae. Merlucciidae is most closely related to Gadidae. Within Merlucciidae, American and Euroafrican clades show similar levels of differentiation to those within Gadinae where Trisopterus and Micromesistius are sister taxa. Genetic distance values for Merluccius subspecies pairs are less than half of those between species, comparable to intra specific differentiation levels in marine fish species.